TUBER OF ETHOMEDICINAL PLANTS BALI, NUTRITIONAL AND ORODENTAL HEALTH - I Gusti Ngurah Alit Wiswasta; I Gusti Ayu Ari Agung; Ria Koesoemawati; I Made Hendra Wijaya; Dewa Gede Agung Gana Kumara (International Journal of Applied Science and Sustainable Development (IJASSD), 2019)
This study is about be use tuber of Bali traditional plants for nutrition and orodental health, were carried out in some place in Bali. This study was carried for three months with purpose to know nutrition, kind and plants species and tuber of plant to be used as a traditional treatment for nutrition and orodental health. The study will carried through literature study, confirmation through interview, and observation; and than to resulting of this study as used as the description method. The data recorded are name of plant as a local name, general name, and scientific name; nutrition and bioactive substance content, the tuber of plant to be useful as a traditional nutrition and bioactive substance to treat the orodental health, with make from tuber. Most parts of the plant used for the traditional orodental nutrition and health is 11 species is the tuber of plant, the most commonly consumed is Curcuma domestica, Caempferia galansa, Curcuma longa, Curcuma purpurascens, Alpinia galanga, Zingiber cassumunar, Zingiber officinale, Zingiber aromaticum, Caempferia rotunda, Ipomoea batatas and Allium cepa. The nutritional content of the tuber of the plant for orodental health is protein, vitamin A, B, C and mineral Mg, K, Ca, Fe, P, I , Na, Zn. The high content of vitamin, mineral, antioxidant and anti-fungi, anti-bacteria and anti-virus in tuber of Bali traditional plants is increase immunity, very good for dental and oral health